2020
DOI: 10.1029/2020je006659
|View full text |Cite
|
Sign up to set email alerts
|

Possible Transient Luminous Events Observed in Jupiter's Upper Atmosphere

Abstract: • Eleven transient bright flashes were observed by the ultraviolet instrument on the Juno mission • The flashes have an average duration of 1.4 ms, are located 260 km above the 1-bar level and are dominated by H 2 emission • The observations are consistent with transient luminous events which occur in the upper atmosphere in response to tropospheric lightning

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 14 publications
(45 citation statements)
references
References 58 publications
5
40
0
Order By: Relevance
“…In Giles et al. (2020), we presented several instances of transient bright flashes observed in the Juno UVS data, and we concluded that these were consistent with TLEs known as elves, sprites, or sprite halos, upper atmospheric responses to tropospheric lightning. The bright spot that we present in this paper differs from the previous bright flashes in two main ways, highlighted in Figure 3.…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…In Giles et al. (2020), we presented several instances of transient bright flashes observed in the Juno UVS data, and we concluded that these were consistent with TLEs known as elves, sprites, or sprite halos, upper atmospheric responses to tropospheric lightning. The bright spot that we present in this paper differs from the previous bright flashes in two main ways, highlighted in Figure 3.…”
Section: Discussionsupporting
confidence: 75%
“…As suggested earlier by the color of the bright spot in Figure 1, the bright spot emission has an unusual spectral shape compared to both the auroral emission and the TLE emission described in Giles et al. (2020). The auroral and TLE spectra are dominated by H 2 emission, and the H 2 Lyman band can be recognized by a double peak at 160 nm.…”
Section: Resultssupporting
confidence: 65%
See 3 more Smart Citations